Clock Drawing Test in acute stroke and its relationship with long-term functional and cognitive outcomes. Issue 5 (4th July 2019) - Champod, Anne Sophie; Gubitz, Gord J.; Phillips, Stephen J.; Christian, Christine; Reidy, Yvette; Radu, Luiza M.; Darvesh, Sultan; Reid, John M.; Kintzel, Franziska; Eskes, Gail A.
Abstract: Objective: The Clock Drawing Test (CDT) is commonly used as a screening tool for the assessment of dementia. The association between the CDT in acute stroke and long-term functional and cognitive outcomes in this population is unknown. The present prospective study is the first to examine if CDT scores in the acute stage after stroke are related to long-term outcomes and to compare the predictive ability of two scoring systems in a large sample of stroke patients. Method: A total of 340 patients admitted to an acute stroke unit were included in the present study. Separate stepwise multiple linear regression analyses were performed with eight independent variables (demographic/pre-stroke variables – age, sex, premorbid functioning; stroke-related variables – stroke severity, localization; cognitive variables – Orientation Test, CDT [2 scoring systems]), and four dependent variables administered one year post-stroke (Barthel Index, modified Rankin Scale, Reintegration to Normal Living index, Global Deterioration Scale). Results: Although both CDT scoring methods were related to all long-term outcome measures, the more comprehensive scoring system was the only baseline variable that significantly explained the variance in outcome measures in all four multiple regression models. Conclusion: Performance on the CDT in acute stroke is related to long-term outcomes including patients' degree of independence in performing activities of daily living, the degree to which they achieved reintegration into daily occupations, and the degree of cognitive decline observed one-year post-stroke. Future studies are needed to clarify the nature of the relationship between different CDT scoring systems and post-stroke outcomes.